Employment and Labor Union Laws in Japan between the 1889 and 1946 Constitutions: A Comparative Study: أفراح محمد علي (Journal of the College of Education for Women, 2021)
This research is based on the descriptive and analytical methodology. The importance of studying labor laws and labor unions in Japan between 1889 and 1946 constitutions is because Japan was out of a feudal phase, and had no idea about the factory system and industrialization in their modern sense before the Meiji era. Generally, its labor system used to be mostly familial, and the economic system was based on agriculture. This called for the enactment of legislations and laws appropriate for the coming phase in Meiji era. Thus, this paper examines the role of Meiji government in enacting labor legislations and laws when he came to power in 1896, and his new constitution in 1889 and the civil code of 1896. It further examines the way Meiji government and the following Japanese governments until the end of World War II did not abide by Meiji laws and stipulations of the constitution with their abusive actions in ending the workers’ strikes and disputes, with the inequality between genders in labor and wages, and the use of child labor in factories in an inhuman way. The paper clarifies the role of the American occupation of Japan (1945-1952) after dissolving Meiji constitution and legislations and the government measures that followed them to enact new legislations, laws and constitution for Japan on November 3, 1946, which was active in May 3, 1947. The paper has concluded that the American occupation policy of Japan was able to avoid the dissidence of millions of Japanese workers, whose level of livelihood was deteriorating after their country lost the war, and convert them from a dissident group against the occupation to a peaceful group which did not target the occupation in their future goals.